The newspaper El Comercio de Cusco: Urban history and Cusco - Calvo Calvo, Rossano (1998)
In 1996, the Cusco newspaper El Comercio commemorated the centenary of its creation. It was thought, for this reason, to review its chronicles in order to reassess the journalistic work carried out in these 100 years. My participation in this project was focused on the local and regional aspects referred to in their chronicles. These have great testimonial value to analyze the pulse of the urban history of Cusco and "cusqueñismo", but above all to properly understand the work of journalism and one of the most prominent newspapers in Cusco, one of the most important Andean cities. from the country.